2021
DOI: 10.5194/acp-21-11453-2021
|View full text |Cite
|
Sign up to set email alerts
|

Increase of nitrooxy organosulfates in firework-related urban aerosols during Chinese New Year's Eve

Abstract: Abstract. Little is known about the formation processes of nitrooxy organosulfates (OSs) by nighttime chemistry. Here we characterize nitrooxy OSs at a molecular level in firework-related aerosols in urban Beijing during Chinese New Year. High-molecular-weight nitrooxy OSs with relatively low H / C and O / C ratios and high unsaturation are potentially aromatic-like nitrooxy OSs. They considerably increased during New Year's Eve, affected by the firework emissions. We find that large quantities of carboxylic-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…Duportéet al observed an OS at 249 (compound 5 in this study) dehydrating to an OS at 231 (compound 6) during MS analysis. 27 On kaolinite, α-pinene derivatives pinonaldehyde (11) and pinonaldehyde dimer (12) are formed 40 and further oxidized to form their respective acids (compounds 13 and 14). Formation of pinonaldehyde and pinonaldehyde dimer upon exposure to kaolinite surfaces is explained in detail in our previous study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Duportéet al observed an OS at 249 (compound 5 in this study) dehydrating to an OS at 231 (compound 6) during MS analysis. 27 On kaolinite, α-pinene derivatives pinonaldehyde (11) and pinonaldehyde dimer (12) are formed 40 and further oxidized to form their respective acids (compounds 13 and 14). Formation of pinonaldehyde and pinonaldehyde dimer upon exposure to kaolinite surfaces is explained in detail in our previous study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Primary biogenic precursors are isoprenes, monoterpenes, sesquiterpenes, and aldehydes. 11 α-Pinene (C 10 H 16 ), a biogenic volatile organic compound, is one of the most abundant atmospheric monoterpenes with an average estimated emission of 66 Tg yr −1 . 12−15 Furthermore, α-pinene-derived OS-, ON-, and NOS-SOA along with oxygenated α-pinene derivatives have been detected in ambient air.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we seek to S4. 54 identify a series of 13 C and 34 S isotopes of OSs and to estimate their corresponding δ 13 C and δ 34 S values at the molecular level in urban aerosols using FT-ICR MS. The 34 S isotopes of aliphatic and non-aliphatic OSs were separated to investigate their precursors and potential formation pathway.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(b−d) Molecular weight and DBE distribution, typical Van Krevelen plots, and molecular corridors and volatility of 13 C and 34 S isotopes of OSs during the heavy-haze period, respectively. The classification criteria for panel c are listed in TableS4 54.…”
mentioning
confidence: 99%